BOLALARDA METABOLIK SINDROM VA SEMIZLIK (METABOLIC SYNDROME IN CHILDREN) - Musakova Shaxnozaxon Ulug'bek qizi; Qobiljonova Sarvinoz Raxmatullo qizi (TADQIQOTLAR, 2026)
Annotation Metabolic syndrome in children represents a serious and increasing global health problem closely associated with the rising prevalence of childhood obesity. This syndrome is defined by a combination of metabolic disorders, including insulin resistance, abdominal obesity, dyslipidemia, and elevated blood pressure, which significantly increase the risk of type 2 diabetes mellitus and cardiovascular diseases in later life. Evidence suggests that unhealthy dietary habits, insufficient physical activity, genetic factors, and environmental influences play a critical role in the development of metabolic syndrome during childhood [1, 2]. Early identification and preventive strategies, such as lifestyle modification and nutritional interventions, are essential to reduce long-term metabolic and cardiovascular complications and to improve overall pediatric health outcomes [3, 4].